Hubungan Antara Pengetahuan Kebahasaan dengan Kemampuan Menulis Naskah Drama Berdasarkan Pengalaman Pribadi Siswa Kelas 11 SMA Negeri 1 Lubuklinggau - Inda Puspita Sari (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2017)
The purpose of this research is to know how the correlation of linguistic knowledge with the ability to write drama script based on personal experience of class 11 students of SMA Negeri 1 Lubuklinggau. This research uses descriptive correlation method. The data was collected by using two variable test. The variables in this study consist of variables X language knowledge, Y)ability to write drama script based on personal experience. To know how the relationship between linguistic knowledge with the ability to write drama script based on personal experience of students of class 11 SMA Negeri 1 Lubuklinggau, using the Product Moment formula rough figures. Hypothesis testing by comparing the amount of r count with rtabe 4l after consulted on product moment value with db df = 34 at 5 percent significant level obtained r table = 0,339 while at significant level 1 percent obtained r table = 0,436. With demikin then r count is bigger than r table. 0.9314 greater than 0.339 for a significant level of 5 percent and 0.959 greater than 0.436 for a significant level of 1 percent. This means that the alternative hypothesis Ha is accepted or proved to be true, that there is a correlation between linguistic knowledge variable X and the ability to write drama script based on personal experience Y variable students of class 11 SMA Negeri 1 Lubuklinggau. Based on the results of research and discussion it can be concluded that there is a relationship between linguistic knowledge and the ability to write drama script based on personal experience of students of class 11 SMA Negeri 1 Lubuklinggau. Keywords: linguistic knowledge, drama, personal experience